3MC syndrome: molecular findings in previously reported and milder patients expand the natural history and phenotypic spectrum. Issue 1 (28th November 2022) - Ashton, Chloe Jade; Perveen, Rahat; Beaman, Glenda; Crisponi, Giangiorgio; González-Del Angel, Ariadna; Garza-Mayén, Gilda; Alcántara-Ortigoza, Miguel Angel; O'Sullivan, James; Clayton-Smith, Jill
Abstract : The 3MC syndromes types 1–3 (MIM#257920, 265050 and 248340, respectively) are rare autosomal recessive genetic disorders caused by pathogenic variants in genes encoding the lectin complement pathway. Patients with 3MC syndrome have a distinctive facial phenotype including hypertelorism, highly arched eyebrows and ptosis. A significant number of patients have bilateral cleft lip and palate and they often exhibit genitourinary and skeletal anomalies. A clinical clue to 3MC syndrome is the presence of a characteristic caudal appendage. Genetic variants in MASP1, COLEC11 and COLEC10 genes have been identified as the causation of this syndrome, yet relatively few patients have been described so far. We consolidate and expand current knowledge of phenotypic features and molecular diagnosis of 3MC syndrome by describing the clinical and molecular findings in five patients. This includes follow-up of two brothers whose clinical phenotypes were first reported by Crisponi et al in 1999. Our study contributes to the evolving clinical and molecular spectrum of 3MC syndrome.